Untargeted metabolomics profiling of purple rice phenolics and their antioxidant activities - Li, Xianbao (2024)
Phenolics in three purple rice varieties were qualitatively and quantitatively analyzed using untargeted metabolomics, and their antioxidant activities were also investigated. Jixuenuo showed the highest antioxidant activity and phenolic content among the three varieties. Ninety-three phenolics across four categories (flavonoids, phenolic acids, stilbenes, and lignans) were identified, with Jixuenuo showing the highest anthocyanin content. Cyanidin-3-O-glucoside (C3G) accounted for over 90% of total anthocyanin content. The volcano plot analysis identified 53 differential phenolics, 22 of which were classified as major. KEGG pathway analysis revealed significant enrichment in flavonoids biosynthesis pathways. Jixuenuo showed significantly enhanced biosynthesis in the pathways for cyanidin, dihydromyricetin, epicatechin, C3G, myricetin, and rutin. Correlation analysis indicated that these flavonoids were significantly positively correlated with antioxidant activity and total phenolic content. These findings suggest that specific flavonoids in Jixuenuo may serve as markers for evaluating the antioxidant potential of purple rice.